TEACHING ENGLISH FOR YOUNG LEARNERS THROUGH ICTs - Dewi, Puspita (LPPM Universitas Bumigora Mataram, 2019)
Nowadays, most people throughout the world learn English because English has an important role in economics, politics, and other aspects, especially for facing free trade in the ASEAN Economic Community (MEA). However, Teaching English as second language becomes more challenging to teach, particularly for young learners. In this case, Information and communication technologies (ICTs) has a pivotal role in assisting teachers in teaching and learning English and for helping students to learn English easier. Numerous scholars, educators and teachers believe that ICT has positive effects in teaching and learning English. Through ICT by incorporating local cultures and values, gender equality, and the others, it will make the activities in classroom to be more interactive and interesting. Language, cultures and IT should be embedded and incorporated. Teachers can encourage children’s motivation and improve their English abilities through ICTs. This reviews some theories of using ICTs by integrating the diversity of cultures and values either local or national and international cultures and values in the teaching and learning process. It can assist teachers to establish their teaching and learning in classrooms to be more effective, interactive, and communicative.